Application of targeted goat grazing in oil palm plantations: Assessment of weed preference, spatial use of grazing area and live weight change - Nobilly, Frisco; Raymond Maxwell, Thomas Manlit; Yahya, Muhammad Syafiq; Azhar, Badrul (Malaysian Palm Oil Board, 2021)
Targeted goat grazing is a promising tool to control competing weeds in crop plantation systems without causing adverse effects on the environment. Here, we investigated the effectiveness of targeted grazing for weed control involving 11 Katjang crossbreed goats in a mature oil palm plantation. We assessed the animal behaviour and management aspects including weed preference, spatial use of grazing area, and body weight change. Asystasia gangetica was the most preferred weed species, followed by Clidemia hirta. Time spent grazing on A. gangetica (45.83-282.91 s) and C. hirta (10.04-49.82 s) by the female goats were different between grazing days (p<0.05). Spatial use between edge and interior areas of grazing plots were not different (p=0.718), meaning goats grazed evenly throughout the grazing plots. Our results revealed that goats fed evenly on the diverse weed community throughout the grazing plots and maintained similar body weight (p=0.488) before and after grazing. Livestock integration with oil palm agriculture in the manner of targeted grazing should be promoted as a part of integrated pest management for reducing weeds. Targeted grazing might be the solution for environmentally sound weed management in sustainable oil palm plantations.